1996
DOI: 10.1007/bf00053823
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble organics in atmospheric particles: A critical review of the literature and application of thermodynamics to identify candidate compounds

Abstract: Although organic compounds typically constitute a substantial fraction of the fine particulate matter (PM) in the atmosphere, their molecular composition remains poorly characterized. This is largely because atmospheric particles contain a myriad of diverse organic compounds, not all of which extract in a single solvent or elute through a gas chromatograph; therefore, a substantial portion typically remains unanalyzed. Most often the chemical analysis is performed on a fraction that extracts in organic solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
923
2
9

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 1,104 publications
(955 citation statements)
references
References 157 publications
(273 reference statements)
21
923
2
9
Order By: Relevance
“…These compounds fall in the lower end of the molecular mass range for major WSOM constituents of PM proposed by Saxena and Hildemann. 47 Calculations showed that log K P values (m 3 air g −1 solvent ) for PYR and FLT determined using these ppLFER models (at 298 K, normalized using the solvent densities) differ by ≤0.3 and ≤0.1 log unit, respectively. We allocated DMSO-air to phase 'A' because it has both the highest water solubility (i.e., 1 × 10 6 compared to 2.19 × 10 5 and 9.78 × 10 5 mg L −1 , respectively; at 298 K) and Abraham "S" descriptor (1.72 compared to 0.70 and 1.31, respectively) and is the least volatile (p L 0 : 81.3 compared to 3.1 × 10 4 and 516 Pa, respectively) among the three candidate surrogates,…”
Section: Pplfer Approach and Model Setupmentioning
confidence: 95%
“…These compounds fall in the lower end of the molecular mass range for major WSOM constituents of PM proposed by Saxena and Hildemann. 47 Calculations showed that log K P values (m 3 air g −1 solvent ) for PYR and FLT determined using these ppLFER models (at 298 K, normalized using the solvent densities) differ by ≤0.3 and ≤0.1 log unit, respectively. We allocated DMSO-air to phase 'A' because it has both the highest water solubility (i.e., 1 × 10 6 compared to 2.19 × 10 5 and 9.78 × 10 5 mg L −1 , respectively; at 298 K) and Abraham "S" descriptor (1.72 compared to 0.70 and 1.31, respectively) and is the least volatile (p L 0 : 81.3 compared to 3.1 × 10 4 and 516 Pa, respectively) among the three candidate surrogates,…”
Section: Pplfer Approach and Model Setupmentioning
confidence: 95%
“…The Köhler theory provides a link between CCN activity and the hygroscopic growth of the aerosol. Because atmospheric aerosols are primarily complex mixtures of organics, inorganics, black carbon (BC), mineral dust, and sea salt, the multicomponent Köhler theory has been suggested to account for the effects of different solute species (mainly organics) on the surface tension [Saxena and Hildemann, 1996;Petters and Kreidenweis, 2007;Wang et al, 2010]. Various laboratory studies have investigated organic compounds and inorganic-organic mixtures to understand the differences in their activation behavior, which arises primarily due to solubility, droplet surface tension, and effects on the mass accommodation coefficient of water.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that certain thermodynamically insoluble species also act as good CCN when present in metastable states or internally mixed with a small percentage of soluble species [Chang et al, 2007]. Although organics constitute a major portion of aerosols (10-70% of the submicron mass of the ambient aerosols), their formation mechanisms, detailed speciation, and roles in influencing the Earth's radiation budget are still not well understood [Saxena and Hildemann, 1996;Turpin et al, 2000;Hallquist et al, 2009;Kanakidou et al, 2005]. Recently, water-soluble organic compounds (WSOCs) have gained increased attention from researchers working on the indirect effect of aerosols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khwaja [1995] cites a long list of literature that supports the role of carboxylic acids, one of the dominant classes of organic compounds found in the atmosphere, in the precipitation acidity observed in both urban and remote areas of the world. Saxena and Hildemann [1996)] note that studies at both rural and urban locations have reported that approximately one fifth to two thirds of the total particulate carbon in the atmosphere consists of water soluble OC.…”
Section: Introductionmentioning
confidence: 99%